Case study of solar PV comparison cost saving at student accommodation. - Ku, Ching Yong; Noranai, Zamri (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Malaysia is located at a strategic location which is in the equatorial region which offers it an advantage in solar energy production. Bistari Hostel at Parit Raja, Johor contains 168 houses and located near the main campus of University Tun Hussein Onn Malaysia (UTHM), which is one of the best accommodations for students along with their university life at UTHM. This study focuses on solar energy harvesting at Bistari Hostel which is to identify the cost electricity can be reduced if solar PV is installed at the building roof of blocks B1, B2, B3, B4, and the parking area of Bistari Hostel. The solar PV modules that will be studied in this paper are produced by Jinko Solar. The energy consumption at Bistari Hostel was taken from Uten Holdings Sdn. Bhd. (the property owner) and estimation of energy usage, if all the houses are rent out, were made. The potential application of the five types of solar PV from Jinko Solar was determined and in this study, the most efficient solar PV are chosen from their ability to generate electricity. The energy-saving if the solar PV is installed at Bistari Hostel is expected to reduce the cost of electricity by more than 25% and the results show that there will be excess electricity generate by the solar PVs. More factors can be included to determine the effectiveness of the solar panels in future study such as the degradation rate and the installation and maintenance cost and the payback period.